IMPROVING THE MANAGEMENT OF THE STATE CADASTRAL VALUATION IN THE RUSSIAN FEDERATION - V. Grigoryev (Управленческие науки, 2016)
The article describes the concept of improving the management of the state cadastre valuation of real estate with the purpose of taxation. The main point of the concept is to replace the present inefficient mechanism of cadastral valuation with the effective continuously functioning system of state cadastral valuation of real estate. The article shows the current negative state in the governmental cadastral valuation management lying in “patchwork”-type character of real estate valuation, lack of coordination of various government agencies in the process, as well as of an indivisible state agency responsible for the quality of the cadastral valuation in the country. This results in an untrue property cadastral value, which is contested juridically and extrajuridically by many taxpayers. The outcome of contesting real estate cadastral value is loss of stability of regional and local budgets and social tension aggravation in the regions.The article formulates a new concept of management of governmental real estate cadastral valuation, based on the implementation of general and specific functions of the governmental cadastral valuation by the Federal agency of state registration, cadastre and cartography (Rosreestr) jointly with the independent assessors. General functions of the governmental real estate cadastral valuation are distributed in the article between individual subdivisions of the Rosreestr; the scheme of system’s functioning has been given.The proposed system of governmental real estate cadastral valuation based on the current organizational structure of Federal registration service management, the subdivision which together with the independent assessors can effectively implement general and specific functions of cadastral valuation and ensure the quality of the property cadastral valuation. Thereby the billows of legal cases contesting the cadastral value will significantly reduce and social tension in the regions, caused by errors in assessing and contesting property cadastral value will decrease.